A FPGA Implementation of the CAR-FAC Cochlear Model - Xu, Ying; Thakur, Chetan S.; Singh, Ram K.; Hamilton, Tara Julia; Wang, Runchun M.; van Schaik, André (Frontiers in Neuroscience, 2018)
This paper presents a digital implementation of the Cascade of Asymmetric Resonators with Fast-Acting Compression (CAR-FAC) cochlear model. The CAR part simulates the basilar membrane’s (BM) response to sound. The FAC part models the outer hair cell (OHC), the inner hair cell (IHC), and the medial olivocochlear efferent system functions. The FAC feeds back to the CAR by moving the poles and zeros of the CAR resonators automatically. We use time-multiplexing and pipeline parallelizing techniques to implement a 70-section, 44.1 kHz real-time CAR-FAC system on an Altera Cyclone V Field Programmable Gate Array (FPGA). We have validated that the system performance matches the mathematical CAR-FAC model. The fully digital reconfigurable CAR-FAC system is stable, scalable, easy to use, and provides an excellent input stage to more complex machine hearing tasks such as sound localization, sound segregation, speech recognition, and so on.